Constructing luminescent particle/MOF composites by employing polyvinylpyrrolidone-modified organic crystals as seeds. Issue 83 (29th September 2016) - Lei, Yilong; Sun, Yanqiu; Zhang, Hongyang; Liao, Liangsheng; Lee, Shuit-Tong; Wong, Wai-Yeung
Abstract : Two types of organic particle/MOF structures, i.e. Znq2 @ZIF-8 core–shell and multiple Znq2 particles on each ZIF-8, can be constructed by modulating the Znq2 –ZIF-8 interfacial energy with PVP. Abstract : We develop a novel and facile chemical reaction route to modulate the crystallization process of luminescent zinc 8-hydroxyquinoline (Znq2 ) particles. Polyvinylpyrrolidone (PVP)-modified octahedral Znq2 micro- and nano-crystals were used as seeds to construct two distinct hybrid structures, i.e., Znq2 @ZIF-8 core–shell and multiple Znq2 particles on each ZIF-8.